2021
DOI: 10.1111/ijcs.12646
|View full text |Cite
|
Sign up to set email alerts
|

Consumer financial literacy and the efficiency of mortgage‐related decisions: New evidence from the Panel Study of Income dynamics

Abstract: This study evaluated the link between financial literacy and household mortgage decisions. To this end, the longitudinal data set for the U.S. population from the Panel Study of Income Dynamics (PSID) was used. Evidence for links between financial literacy levels and (1) mortgage uptake, (2) mortgage interest rates and (3) mortgage refinancing decisions were examined using the two waves (2015 and 2017) of PSID data, combined with the 2016 PSID supplementary questionnaire examining the measured financial litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 80 publications
(98 reference statements)
1
18
0
Order By: Relevance
“…The promotion and provision of financial literacy education should be considered an important tool for increasing well-being at the onset of a credit decision. Financial literacy has been already proven to facilitate a better selection of credit products (Fornero et al 2011) and decrease the cost of debt (Bialowolski et al 2020;Gathergood and Weber 2017). Thus, it can translate into higher satisfaction with credit and consequently with life in general.…”
Section: Promote Financial Literacymentioning
confidence: 99%
“…The promotion and provision of financial literacy education should be considered an important tool for increasing well-being at the onset of a credit decision. Financial literacy has been already proven to facilitate a better selection of credit products (Fornero et al 2011) and decrease the cost of debt (Bialowolski et al 2020;Gathergood and Weber 2017). Thus, it can translate into higher satisfaction with credit and consequently with life in general.…”
Section: Promote Financial Literacymentioning
confidence: 99%
“…FL was estimated, for instance, to explain about 30%-40% of retirement wealth inequality in the United States (Lusardi et al, 2017). A low level of FL was linked to sub-optimal financial decisions resulting in high-cost borrowing (Disney & Gathergood, 2013;Lusardi & Tufano, 2015;Mottola, 2013;Pak, 2018), debt accumulation (Lusardi & Tufano, 2015;Stango & Zinman, 2009), poor mortgage terms (Bialowolski et al, 2020), mortgage delinquency (Gerardi, 2010;Kim et al, 2020), late credit card payments (Hamid & Loke, 2021), and relatively low likeliness of stock market participation (Yoong, 2011).…”
Section: Relationship Between Actual and Perceived Literacy Skills And Financial Outcomesmentioning
confidence: 99%
“…The literature on the impact of financial literacy on credit choices and debt management behavior is more extensive. Several studies revealed that more financially literate consumers are more likely to be holders of secured debt, mostly mortgages (Disney and Gathergood, 2011;Brown and Graf, 2013;Feng et al, 2019;Bialowolski et al, 2020). Bialowolski et al (2020) provides arguments that mortgage borrowing can be considered healthy financial behavior.…”
Section: Financial Education and Its Effectivenessmentioning
confidence: 99%
“…Several studies revealed that more financially literate consumers are more likely to be holders of secured debt, mostly mortgages (Disney and Gathergood, 2011;Brown and Graf, 2013;Feng et al, 2019;Bialowolski et al, 2020). Bialowolski et al (2020) provides arguments that mortgage borrowing can be considered healthy financial behavior. At the same time, the correlation between financial literacy and the likelihood of holding unsecured (i.e., riskier and more costly) debt is absent (Feng et al, 2019) or negative (Brown and Graf, 2013).…”
Section: Financial Education and Its Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation